Work stress, eating habits and anthropometric nutritional status in administrative and operational workers of a private clinic in Lima, 2018 - Manzano Huaracallo, Juan (2019)
Objective: To determine the relationship between work stress, eating habits and anthropometricnutritional status in administrative and operational workers of a private clinic in Lima. Methodology:Study of quantitative approach, cross-section, non-experimental design, and correlational descriptivetype. A sample of 150 adult workers, divided into administrative and operational, Instruments: Wasselected by intentional non-probabilistic sampling. Surveys of ILO labor stress and eating habits wereapplied, in addition to anthropometric nutritional evaluation. Results: Participants showed low levelsof work stress, with 93.3% for operational workers and 94.7% for administrative workers; they alsopresented adequate eating habits in 72% and 66.7% respectively; Finally, 44% of operational workerswere overweight, while 60% of administrative workers had a normal BMI. It was shown that for theadministrative staff there is a statistically significant correlation between the variables (p <.05), but notfor the operating group (p> .05). Conclusion: work stress and eating habits of administrative workershad an impact on their nutritional status, but not on operational workers, however, both groups hadlow levels of stress and adequate eating habits; Therefore, healthy work environments could have apositive impact on their health.